Editorial Vol.11(1) - Editor, The (Nepal Journal of Dermatology, Venereology & Leprology, 2013)
DOI: http://dx.doi.org/10.3126/njdvl.v11i1.7928 Nepal Journal of Dermatology, Venereology & Leprology Vol.11(1) 2013